2016
DOI: 10.1002/jcp.25436
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐to‐Mesenchymal Transition in Paclitaxel‐Resistant Ovarian Cancer Cells Is Downregulated by Luteolin

Abstract: Ovarian cancer (OVCA) is the deadliest of all gynecological cancers which is attributed to late presentation, persistence, and development of chemoresistance. The objectives were to evaluate the association between OVCA paclitaxel-resistance and epithelial-to-mesenchymal transition (EMT) and to determine the capability of luteolin to chemosensitize OVCA cells. X10 and X22 cells were 11.8-25.3-fold and 7.8-8.6-fold resistant to paclitaxel than 1AP cells. X10 and X22 cells exhibited a mesenchymal phenotype, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 49 publications
(49 reference statements)
2
30
0
Order By: Relevance
“…An FCM measurement revealed positive for CD90, CD105, and PDGFR-β and negative for CD31 and CD45 indicating that the majority of MLpvNG2 + cells have similar expression patterns to niBM-MSCs [32] . The expressions of mesodermal markers of vimentin, N-cadherin, Col1a1, Prrxl, Snail [33] and the ability to differentiate into mesodermal lineages that are consistent with those of other studies that characterized MSCs derived from multiple sources [34] , indicating that MLpvNG2 + cells originate from a mesenchymal source [35,36] . As oct3/4 is a main marker for embryonic stem cells [37] and its higher expression in MLpvNG2 + cells than in niBM-MSCs might suggest that MLpvNG2 + cells may be more "stem" than niBM-MSCs, needs to be further investigated.…”
Section: Discussionsupporting
confidence: 88%
“…An FCM measurement revealed positive for CD90, CD105, and PDGFR-β and negative for CD31 and CD45 indicating that the majority of MLpvNG2 + cells have similar expression patterns to niBM-MSCs [32] . The expressions of mesodermal markers of vimentin, N-cadherin, Col1a1, Prrxl, Snail [33] and the ability to differentiate into mesodermal lineages that are consistent with those of other studies that characterized MSCs derived from multiple sources [34] , indicating that MLpvNG2 + cells originate from a mesenchymal source [35,36] . As oct3/4 is a main marker for embryonic stem cells [37] and its higher expression in MLpvNG2 + cells than in niBM-MSCs might suggest that MLpvNG2 + cells may be more "stem" than niBM-MSCs, needs to be further investigated.…”
Section: Discussionsupporting
confidence: 88%
“…Many epithelial tumors undergo EMT, which facilitates their invasion. Longterm treatment with anti-tumor drugs, such as paclitaxel [ 26 ] and cisplatin [ 27 ], causes tumor resistance and EMT, but some agents can reverse the EMT induced by anti-tumor drugs [ 26 , 27 ]. It has been shown that NF-κΒ activation is one response of tumor cells to some drugs, and that it contributes to EMT [ 8 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants rich in luteolin have been used in Chinese traditional medicine to treat various diseases, such as hypertension, inflammatory disorders, and cancer [3, 4]. The anti-cancer activities of luteolin have been demonstrated in many cancer cells, such as pancreatic cancer, prostate cancer, breast cancer, colorectal cancer, and ovarian cancer [5-8]. In addition, luteolin could upregulate the mRNA expression level of intercellular adhesion molecule-1, a tumor suppressor gene [9], in mouse H22 hepatoma cells [10].…”
Section: Introductionmentioning
confidence: 99%